1991
DOI: 10.1056/nejm199104113241501
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Prophylactic Ganciclovir for Cytomegalovirus Pulmonary Infection in Recipients of Allogeneic Bone Marrow Transplants

Abstract: In recipients of allogeneic bone marrow, asymptomatic CMV infection of the lung is a major risk factor for subsequent CMV interstitial pneumonia. Prophylactic ganciclovir is effective in preventing the development of CMV interstitial pneumonia in patients with asymptomatic infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
243
3
6

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 617 publications
(255 citation statements)
references
References 25 publications
3
243
3
6
Order By: Relevance
“…Prophylaxis and pre-emptive therapy are now used widely in the management of the bone marrow transplant recipient. [12][13][14][15][16][17] In our study all allograft recipients received acyclovir prophylaxis, but the patients were not routinely given pre-emptive ganciclovir therapy. The observation that viral load was significantly higher in patients treated with GCV can be explained by the fact that the majority of patients were given GCV therapy based on clinical assessment of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylaxis and pre-emptive therapy are now used widely in the management of the bone marrow transplant recipient. [12][13][14][15][16][17] In our study all allograft recipients received acyclovir prophylaxis, but the patients were not routinely given pre-emptive ganciclovir therapy. The observation that viral load was significantly higher in patients treated with GCV can be explained by the fact that the majority of patients were given GCV therapy based on clinical assessment of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These assays have allowed patient management strategies to be developed so that pre-emptive therapy is now widely used. 12,13 In addition, placebo-controlled trials of ganciclovir (GCV) and acyclovir (ACV), have demonstrated that these drugs can decrease HCMV infection and, in some cases, disease when used prophylactically. [14][15][16][17] Nevertheless, HCMV continues to cause significant disease in bone marrow recipients, necessitating continued routine surveillance for HCMV coupled with specific diagnostic testing in target organs such as lung, liver and gut.…”
mentioning
confidence: 99%
“…Two patients excreted CMV prior to engraftment and were not included 49. 16 Patients in whom CMV was detected were randomised to receive ganciclovir or to be monitored without treatin the analysis. prevented.…”
mentioning
confidence: 99%
“…detected in bronchoalveolar lavage at day 35 significantly Meyers et al 9 showed that aciclovir used alone and reduced the probability of CMV pneumonia from 70% in administered from conditioning until 30 days post-BMT the control group to 10% in the treated group. 16 This has reduced the incidence of CMV disease. In that study, CMV led to the widespread use of pre-emptive therapy with gandisease included CMV pneumonia, and the isolation of ciclovir.…”
mentioning
confidence: 99%
See 1 more Smart Citation